REAL FRAUDS FOUND IN NOT-FOR-PROFITS - DENNIS, LYNDA (Aicpa Ser., 2020)
Due to the nature of not-for-profits, fraud may be more common than it seems. This book shows how to recognize red flags of fraud, including cyber fraud. It offers a comprehensive learning approach using real-world examples, explanations of audit standards, and informative case studies that analyze several unique frauds which occurred in the not-for-profit industry. Key topics covered are: misappropriation of benefits, pledges and contributions, cyber fraud, and grant expense allocations.